2022
DOI: 10.3390/sym14061216
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Stage Siamese Network Model for Offline Handwritten Signature Verification

Abstract: Offline handwritten signature verification is one of the most prevalent and prominent biometric methods in many application fields. Siamese neural network, which can extract and compare the writers’ style features, proves to be efficient in verifying the offline signature. However, the traditional Siamese neural network fails to represent the writers’ writing style fully and suffers from low performance when the distribution of positive and negative handwritten signature samples is unbalanced. To address this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 41 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…The handwriting discrimination method proposed in this paper presents higher classification success compared to the methods given in [14,16], as well as almost all the other methods presented in the literature given in the Introduction.…”
Section: Classification Performance Comparisonmentioning
confidence: 77%
See 1 more Smart Citation
“…The handwriting discrimination method proposed in this paper presents higher classification success compared to the methods given in [14,16], as well as almost all the other methods presented in the literature given in the Introduction.…”
Section: Classification Performance Comparisonmentioning
confidence: 77%
“…This survey examines symmetrical neural network architectures-Siamese and triplet. Offline handwritten signature verification is one of the most prevalent and prominent biometric methods in many application fields [16]. This study proposes a twostage Siamese neural network model for accurate offline handwritten signature verification with two main ideas: (a) adopting a two-stage Siamese neural network to verify original and enhanced handwritten signatures simultaneously and (b) utilizing the focal loss to deal with the extreme imbalance between positive and negative offline signatures.…”
Section: Introductionmentioning
confidence: 99%
“…In the training process, these two types of networks use two different loss functions: a contrastive loss function in the twin network architecture, and a triplet loss function in the triplet architecture. Applications of Siamese networks include object tracking [ 32 ], face recognition [ 33 ], and signature verification [ 34 ]. In the hyperspectral image domain, research can be found in the application areas of image classification [ 35 ] and object/target detection [ 36 , 37 ].…”
Section: Related Workmentioning
confidence: 99%
“…The distance measure in new space is then adopted to evaluate the similarity of two inputs. Siamese network has been successfully adopted in many realms, such as semantic similarity analysis [24], handwriting font recognition [25], and visual tracking algorithm [26]. Therefore, it is of great significance in many mission-critical applications.…”
Section: Siamese Networkmentioning
confidence: 99%